2003
DOI: 10.4319/lo.2003.48.4.1547
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of particulate, colloidal, and dissolved mercury in San Francisco Bay estuary. 2. Monomethyl mercury

Abstract: The phase speciation and estuarine behavior of monomethyl mercury (MeHg) were determined in surface waters of the San Francisco Bay estuary in September-October 2000 (low flow) and March 2001 (high flow). Colloidally associated MeHg was isolated using a cross-flow ultrafiltration technique with a nominal molecular weight cutoff of 1 kDa. Filter-passing MeHg was 57 Ϯ 18% of the MeHg in unfiltered water in the fall and 39 Ϯ 12% in the spring. Colloidal MeHg averaged 34 Ϯ 11% of the filter-passing MeHg in the fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
38
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 26 publications
9
38
2
Order By: Relevance
“…Ultrafiltration was carried out with ϳ2 liters of sample and a concentration factor (CF, the initial volume/retentate volume) of ϳ15 was used throughout the present study. Additional details on membrane cleaning and ultrafiltration protocol are reported in Choe and Gill (2001 Table 2). The average retention coefficients (R C , the ratio of retentate concentration to initial concentration) of rhodamine 6G and vitamin B-12 were 0.22 (n ϭ 2) and 0.81 Ϯ 0.02 (n ϭ 5), respectively.…”
Section: Study Area-sanmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafiltration was carried out with ϳ2 liters of sample and a concentration factor (CF, the initial volume/retentate volume) of ϳ15 was used throughout the present study. Additional details on membrane cleaning and ultrafiltration protocol are reported in Choe and Gill (2001 Table 2). The average retention coefficients (R C , the ratio of retentate concentration to initial concentration) of rhodamine 6G and vitamin B-12 were 0.22 (n ϭ 2) and 0.81 Ϯ 0.02 (n ϭ 5), respectively.…”
Section: Study Area-sanmentioning
confidence: 99%
“…The major focus of this work is to characterize the size fractionation, distribution, transportation, and fate of Hg and to examine the importance of natural colloidal material on the speciation of Hg. The related study of MeHg is presented separately in this issue (Choe and Gill 2003).…”
mentioning
confidence: 99%
“…Data from the northern reach of San Francisco Bay (Choe and Gill 2003;Choe et al 2003) along with field data from other studies indicate that phytoplankton can affect mercury cycling. For example, Choe et al (2003) found a relationship between chlorophyll a (Chl a) and particulate Hg T in some seasons in North Bay.…”
mentioning
confidence: 91%
“…The combined mercury inputs from the Sierra Nevada and the Coast Range contribute up to several hundred kilograms of mercury to the estuary every year, far more than inputs from contemporary sources (e.g., atmospheric deposition, wastewater treatment plants, and surface-water runoff) (Domagalski 2001;Thomas et al 2002;Conaway et al 2003). Although the cycling of this mercury in the estuary has been previously studied (Choe and Gill 2003;Choe et al 2003;Conaway et al 2003), the role of phytoplankton in mercury cycling needs further investigation (Choe et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation